Chong Chu Le - Chong, Chu Le (2014)
The global economic environment is experiencing uncertainties and the strategic responses of third party logistics (3PL) in Malaysia are not precluded. With the 3PL industry experiencing growing demands of 3PL users and the emergence of more 3PL service providers, these have created further competition within the 3PL industry to attract user firms. This requires 3PL firms to review their strategies to become more competitive. This study focused on the evaluation of external and internal environment followed by strategic choices made by 3PL firms in Malaysia to produce operational performance achieving financial performance in the wake of economic global uncertainties. The 3PL firms strategic positioning choices are low costs and differentiation yielding operational performance of cost and service to achieve financial performance. A composite model was studied based on both perspectives of Resource-based view and Market-based view. The findings show both the external and internal environment influence operations emphases and operational performance leading to financial performance. This study has also found 10 full paths in the model beginning from either external or internal environment through operations emphases and operational performance driving financial performance of 3PL firms. These full paths indicate RBV and MBV are complementary rather than competing frames. In this uncertain global economic environment, firms exercise both cost and service capabilities as their strategies. This finding is supported by the theory of cumulative capabilities.